Efficacy of the feed additives consisting of Enterococcus faecium ATCC 53519 and E. faecium ATCC 55593 for all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the efficacy of two technological additives consisting of Enterococcus faecium strains ATCC 53519 and ATCC 55593, respectively. The additives are intended for use with all types of fresh materials and for all animal species at a proposed minimum concentration of 1 × 107 colony forming units (CFU) of E. faecium ATCC 53519/kg forage or 5 × 106 CFU of E. faecium ATCC 55593/kg forage. In a previous opinion, the FEEDAP Panel could not conclude on their efficacy since the dry matter content of the ensiled materials at the end of the experiments was not corrected for volatiles, which led to an unreliable estimation of the dry matter loss, and the lack of positive effects on any of the other parameters. The supplementary information submitted by the applicant included updated data on the pH values and the dry matter loss corrected for volatiles. However, the estimation of the dry matter loss corrected for volatiles was wrongly calculated and thus, was not considered for the assessment of the efficacy of the additive. Considering the lack of effect on any other fermentation parameter, the Panel could not conclude on the efficacy of the additive to improve the production of silage under the proposed conditions of use.